Gramsci and Sorel: Scission Spirit and Intellectual and Moral Reform - Del Roio, Marcos [UNESP] (My University, 2022)
The purpose of this chapter is to demonstrate how the theoretical category of intellectual and moral reform is malleable and may have variable meanings. The idea is to rescue the notion of intellectual and moral reform connected with the notions of common sense and a historical bloc through an elaboration that begins with Vico. Although rarely addressed in literature, the hypothesis is that the influence of Vico’s historicism is relatively strong in Gramsci’s work, with Sorel’s sensitive mediation.